A benchmark test for validating 3D simulation methods for delamination growth under quasi-static and fatigue loading. (15th February 2019) - Carreras, L.; Renart, J.; Turon, A.; Costa, J.; Bak, B.L.V.; Lindgaard, E.; Martin de la Escalera, F.; Essa, Y.
Abstract: Models for simulating interlaminar crack growth in composites under static and fatigue loads are rarely validated with experimental data different from simple standard tests where the crack front propagates with a uniform shape. The underlying reason for not making use of more realistic experimental data, where the crack front shape changes during the delamination growth, is the lack of well-controlled benchmark cases. This work introduces a comprehensive benchmark case consisting of a double cantilever beam (DCB)-like specimen with partially reinforced arms. A complete set of elastic and fracture properties for the material and a detailed description of load-displacement curves and crack front geometries, monitored with X-ray radiography, is provided. The benchmark case generates a rich phenomenology of crack advance in terms of varying crack growth rate and front shape, while being geometrically simple enough to be simulated.